النثر في عصر النهضة العربية من عام(1850-1916م) (الفن الروائي في سورية ولبنان أنموذجاً) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يعمدُ البحث إلى دراسة الرواية في سورية ولبنان إبان النهضة العربيّة من عام 1850إلى عام 1916م، وذلك بهدف الكشف عن تحققات هذا الفنّ في مجتمع النهضة العربيّة، ومن خلال الربط بين بواكير هذا الفنّ والمنجز النهضويّ العربيّ منذ النصف الثاني للقرن التاسع عشر، إذ ساعدت الرواية على نشر فكر النهضة والتنوير، وتجذيره في بنية المجتمع العربيّ وضمن آليات تفكيره، وقادت الحراك الاجتماعيّ ضد التخلف والاستبداد، وفي سبيل تحقيق مجتمع التمدن والتنوير. جاءت الرواية في عصر النهضة بوصفها أحد الفنون النثرية الجديدة، وعبّرت عن خصوصيتها بما تمثله من تجديد على صعيد الشكل والمضمون، وبما تحمله من معطيات جذب لجمهور القراء الذي ملّ الإطناب والزخرف اللغويّ والبلاغة التقليدية، واتجه إلى تذوق الجديد بعد أن أحسّ  بالدهشة والاستلاب نتيجة المقارنة بين حاضره المتخلف وماضي أمته من جهة، وبين حاضره المتأخر الجامد وحاضر الغرب المتقدم من جهة ثانية. وكان لابدّ من فعل يستنهض الأمة، ويُعينها على السير في طريق جديد، ساهمت الأقلام المتنورة في تعبيده، ووضع خارطة جديدة من القيم والمفاهيم العصرية له، وتكوين جهاز مفاهيميّ جديد للمجتمع الجديد، الذي قد تصح تسميته بمجتمع الرواية والتنوير. This research aims at studying the Novels in Syria and Lebanon in the Arabic Renaissance, between 1850 and 1916 AD. The research targets revealing the materialization of this art in the society of the Arabic Renaissance, through connecting the early beginnings of this art and the Arabic Renaissance outcome. The Novel, then, helped in spreading the Renaissance thinking and enlightenment and firmly establishing it in the structure of the Arabic society and the mechanism of its thinking. It leads to the social movement against backwardness and arbitrariness, in process of reaching the society’s civilization and enlightenment. The Fight between the old and the new to intensify the presence of the Novel as it presents the renovation in Form and Context and holds elements of attraction to the readers who are fed up of expatriation and linguistic adornment and traditional eloquence and who tend to taste the new after they feel astonished as they compare between their backward present and the past of their nation; and between their late solid present and the advanced present of the west on the other hand. there should be an act that  awakens the nation   and enables it to go in a new way that was paved by the enlightened pens, and to put a new map   of modern values and ideas with new understanding of the new society which it may be named as the society of the Novel and enlightenment.